1979
DOI: 10.1017/s0043174500044520
|View full text |Cite
|
Sign up to set email alerts
|

Seedbed Tillage and Herbicide Influence on Soybean (Glycine max) Weed Control and Yield

Abstract: Twenty herbicide treatments were evaluated on conventional-till (plow, disc, and harrow), minimum-till (disc only), and no-till planted soybeans [Glycine max(L.) Merr.] from 1976 through 1978 at the Belleville Research Center in St. Clair County, Illinois. The soil type was a Weir silt loam (Typic Ochraqualf) characterized by poor internal drainage and 1.2% organic matter. Weed population by species, weed control, and soybean population, injury, and yield were obtained. Fall panicum (Panicum dichotomiflorumMic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
3

Year Published

1987
1987
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 5 publications
(4 reference statements)
7
92
0
3
Order By: Relevance
“…30% residue (data not shown). This supports previous reports that have suggested that horseweed is well adapted to no-till systems (Bhowmik and Bekech 1993;Brown and Whitwell 1988;Buhler and Owen 1997;Kapusta 1979;Weaver 2001).…”
Section: Resultssupporting
confidence: 92%
“…30% residue (data not shown). This supports previous reports that have suggested that horseweed is well adapted to no-till systems (Bhowmik and Bekech 1993;Brown and Whitwell 1988;Buhler and Owen 1997;Kapusta 1979;Weaver 2001).…”
Section: Resultssupporting
confidence: 92%
“…First year suppression by tillage and herbicides has been recognized in conventional agricultural settings (Kapsuta, 1979). The failure of horseweed to persist in abundance for more than a single year in any given treatment combination may result from either competitive exclusion by more aggressive early successional species or poor growth in its own residue (Keever, 1950;Tremmel and Peterson, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Pleasant & Schlater 1994). Results of studies on weed community dynamics under these conservational agricultural practices are, however, somewhat inconsistent within and among studies (Kapusta 1979; Stevenson et al . 1997; Swanton et al .…”
Section: Introductionmentioning
confidence: 99%